Planejamento de sistemas de distribuição de energia elétrica de média tensão através de um algoritmo de busca dispersa - Pádua, Súzan Grazielle Benetti de [UNESP] (2014)
In this work the problem of Planning Electric Power Distribution Systems (PEPDS) of Medium Voltage is formulated in three mixed integer nonlinear programming (MINLP) models. The first model performs the static short-term planning that is to determine which lines will be installed and/or reconductive and substations which will be built and/or allowing repotentiated reconfigure the existing network. In this context, the mathematical model is mono objective and minimizes installation costs of new equipment and operating costs of the system subject to a set of physical, operational and economic constraints. The second model is multistage and performs dynamic long-term planning based on the same actions in planning the static model, but it defines when these actions are performed. The third model is multi objective, and it perform the dynamic long-term planning at different stages of considering investments and operating costs that it includes costs of network reliability expressed in terms of unserved energy. This way to solve these models are proposed different versions of Scatter Search (SS) algorithm, two adapters for the solution of static models of short term and long term dynamic multi objective mono, and third goal. The BD is an evolutionary search technique with a flexible structure which allows the development of diverse implementations of changeable degrees of complexity. As detailed contribution are all key steps of the algorithm in the application of the three models of the problem PEPDS using the additive sequential encoding algorithm and a heuristic for efficient selection of drivers. The method is calibrated using a testing systems of 54 buses through various simulations literature system. SS is exposed presenting optimal competitive good quality solution for mono objective to multi objective models and model. It is capable of finding a set of efficient solutions with commitment ...